Research on Proppant Optimization and Field Test of Ultra-Deep Tight Conglomerate Sandstone Reservoir - Wu, Baocheng; Xiao, Fengchao; Kong, Mingwei; Wang, Bin; Zhang, Shicheng (Frontiers in Energy Research, 2022)
Efficient development of deep tight reservoirs in the southern margin of Junggar Basin requires stimulation technology, and effective propped hydraulic fractures are the key to successful stimulation. To optimize the proppant selected for reservoir stimulation, the important parameters of proppant selection were determined through the proppant conductivity evaluation experimental study and field test, considering the influences of high temperature and high closure pressure. The results show that closure pressure, temperature and sand concentration have a great influence on the conductivity of the proppant. The high temperature causes more fine particles to break up and lower proppant-pack permeability. Over the long term, the Scenario B placement pattern has the advantage, and increasing the proppant placement concentration is conducive to the long-term conductivity of the fracture. During the operation of the test well, the combined particle size proppant was pumped stably, and the fractures were effectively propped. No proppant flowing back was observed in the test production after the fracturing, which achieved the purpose of the evaluation well, provided support for the large-scale development of subsequent development wells, and ensured orderly development.